# Simplify tan(csc^-1(x))?

• Simplify tan(csc^-1(x))?

Solution Preview : (tan x csc x)/ sec x tan*csc*1/sec |rearrangement sin/cos*csc*1/sec |tan=sin/cos sin/cos*1/sin*1/sec |csc=1/sin sin/cos*1/sin*cos |sec=1 ...
Positive: 20 %
Simplify (csc(-x))/(1+tan(x)^2) Rearrange terms. Apply pythagorean identity. Factor out of . ... Simplify. Tap for more steps... Divide by to get . Convert ...
Positive: 17 %

### More resources

... (x y) = (tan x tan y) / (1 tan x tan y) sin(2x) = 2 sin x cos x cos(2x ...
Positive: 20 %
simplify the expression csc(-x) 1+tan^2(x)Hint: for the first one. sin(x) ... I'm not sure how you got csc(-x) is sin(x)tan(x) myininaya ...
Positive: 15 %
tan x = sin x/cos x: equation 1: cot x = cos x/sin x: equation 2: sec x = 1/cos x: equation 3: csc x = 1/sin x: equation 4: cot x = 1/tan x: equation 5 ...
Positive: 1 %
Tan(-x)csc(-x) over sec(-x)cot ... For the first part we have Tan = Sin / Cos CSC = 1/ Sin Hence Tan(- x) * csc (-x ... Trigonometric tutorial simplify a ...
Positive: 10 %

Anonymous51161
Create new account

Discover Questions